Governing health data across changing contexts: a focus group study of citizen's views in England, Iceland, and Sweden - Shah, N; Viberg Johansson, J; Haraldsdóttir, E; Bentzen, HB; Coy, S; Mascalzoni, D; Jónsdóttir, GA; Kaye, J (Elsevier, 2021)
BACKGROUND: The governance structures associated with health data are evolving in response to advances in digital technologies that enable new ways of capturing, using, and sharing different types of data. Increasingly, health data moves between different contexts such as from healthcare to research, or to commerce and marketing. Crossing these contextual boundaries has the potential to violate societal expectations about the appropriate use of health data and diminish public trust. Understanding citizens' views on the acceptability of and preferences for data use in different contexts is essential for developing information governance policies in these new contexts.